Decolonizing Desires and Unsettling Musicology: A Settler’s Personal Story of Researching and Teaching Indigenous Music at an American University - Woloshyn, Alexa (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2019)
For those of us with decolonial desires, the university classroom is a potential space of disruption and reorganization. Our courses, course materials, teaching tools, students, and our own bodies and minds are all technologies that can subvert the colonial machine (la paperson 2017). In the first section, I contextualize my decolonial desires as a non-U.S.-citizen settler Canadian musicologist in the United States. The work of David Garneau, Aileen Moreton-Robinson, Andrea Smith, Eve Tuck, and K. Wayne Yang illuminates my positionality and power. In the second section, I provide an example of one way I’m disrupting the typical curricula and classroom experiences in a Euro-American classical music school. I discuss my course entitled “North American Indigenous Music Seminar” (NAIMS), including the course structure and content, and decolonizing strategies. Student responses to interviews about the course are interspersed with the discussion of my seminar plans and challenges to claims of “decolonization.” Their responses reveal some successes and many limits for anti-colonial and decolonial work in a single-semester course.